Thermoplastic Materials : Properties, Manufacturing Methods, and Applications. - Ibeh, Christopher C. (Taylor and Francis, 2014)
Practical and affordable, thermoplastics account for more than 90 percent of all plastic materials manufactured. That so many varieties are now available, speaks to the idea that while there is no one perfect material, it is possible to find a material that fits for every application. However, selecting that right material is no small challenge. Answering the needs of manufacturers and product developers, Thermoplastic Materials: Properties, Manufacturing Methods, and Applications provides all the information required to confidently select the right thermoplastic for any application. Based on a.